Membangun Nilai Kasih Persahabatan dalam Pemberian Kerbau atau Babi dalam Upacara Rambu Solo’ - Lampi, Yayu Astuti (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
Toraja One of the cultures that is popular for its exquisite culture both inside and outside of Indonesia. The Rambu Solo’ ceremony, a death event that is widely celebrated in Toraja, is one of the most well-known. There is a tradition in the ritual